Effectiveness of Pain Management Educational Program on Nurse's knowledge toward Chest Pain Management for Patients with Acute Myocardial Infarction - Hadeer Naeem Abdul-Hussein; Wafaa Abd Ali Hattab (Kufa Journal for Nursing Sciences)
Background: Pain management is a compelling and universal requirement in nursing care; despite significant progress, untreated pain's adverse physiological and psychological effects are still largely unresolved, especially for acute myocardial infarction patients.